Study on extended reality enhancement technology in 5G-Advanced - XIAO Yang (Dianxin kexue)
With the rise of the metauniverse, extended reality has become the multimedia application technology vigorously promoted by the industry. To realize extended reality, it is necessary to enhance the existing wireless network technology to meet the requirements of extended reality services. Firstly, the characteristics of extended reality technology and standard progress in 3GPP were analyzed. In addition, the challenges posed by extended reality services to the 5G-Advance network were explored. To meet the challenges posed by extended reality services, the XR-awareness mechanism, power saving enhancement mechanism, and capacity improvement technologies were investigated. Specifically, based on the packet data unit related parameters, jitter, etc. assistance information, the network can be aware of the XR traffic. In addition, the power consumption can be reduced by introducing the non-integer discontinuous reception mechanism and the playout buffer. And the capacity can be improved by introducing the new buffer status table and enhanced configured grant. Finally, the simulation results and performance analysis show that the proposed enhancement mechanisms can better support the extended reality services.